A method for preparing Zn2Co3(OH) by microwave irradiation 10 ·H2O nanoparticle material method

The preparation of Zn2Co3(OH)10·H2O nanoparticle materials through microwave radiation method has solved the problems of complex preparation methods, slow reaction speed and low yield in the existing technology, and achieved efficient and excellent electrolytic water catalytic performance, providing a new way for the production of clean energy hydrogen.

CN116177613BActive Publication Date: 2025-02-28SUZHOU UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310037837.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-07
Publication Date
2025-02-28
Estimated Expiration
2043-01-07

AI Technical Summary

Technical Problem

The existing Zn2Co3(OH)10·H2O material preparation methods have problems such as complex operation, slow reaction speed and low yield, and it is difficult to meet the efficient demand of electrolytic catalyst materials in the production of clean energy hydrogen.

Method used

The Zn2Co3(OH)10·H2O nanoparticle material was prepared by microwave radiation. By adjusting the reaction time, temperature, molar ratio of reactants, and other conditions, the micromorphology of the target product was regulated and the quality and yield of the material were improved.

Benefits of technology

It has achieved high-quality preparation of Zn2Co3(OH)10·H2O material, with regular morphology, small particle size and excellent catalytic performance, greatly improving the hydrogen yield during the electrolysis process, and providing a new way for the research and development of electrocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177613B_ABST
    Figure CN116177613B_ABST
Patent Text Reader

Abstract

A method for preparing Zn2Co3(OH) by microwave irradiation 10 The method of preparing Zn2Co3(OH)2O nanoparticle material is to use analytical pure Co(NO3)2·6H2O, ZnSO4·7H2O and 2-methylimidazole as reaction raw materials, deionized water as solvent, and cetyltrimethylammonium bromide (CTAB) as surfactant by microwave radiation method. 10 ·H2O material. The microwave radiation method used in this patent is simple to operate and has concentrated energy, which is beneficial to improving the reaction rate and Zn2Co3(OH) 10 The XRD and SEM images of the target product fully prove that the preparation method described in this patent can obtain Zn2Co3(OH) with regular morphology and uniform particle size. 10 ·H2O material; the target product prepared by this patent is Zn2Co3(OH) 10 H2O materials can significantly catalyze the water electrolysis process, thereby increasing the yield of clean energy hydrogen, providing a new approach for the research and development of electrocatalysts and having potential research and application value.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] [Technical Field]: The target product of the present invention is mainly used in the field of water electrolysis catalyst materials, and particularly relates to a method for preparing Zn2Co3(OH) by microwave radiation. 10 · Methods of H2O nanoparticle materials.

[0002] [Technical background]: Metal Organic Frameworks (MOFs) have attracted much attention from researchers in the past decade due to their ultra-high porosity, surface area, uniform and adjustable pores, and fully exposed active sites. MOFs materials have excellent performance in batteries, supercapacitors, catalysis, gas storage and separation, sensors and other fields (Meng J, Liu X, Niu C. Advances in metal-organic framework coatings: Versatile synthesis and broad applications [J]. Chemical Society Reviews, 2020, 49 (10): 3142-3186.).

[0003] Zn2Co3(OH) 10 H2O is one of the typical representatives of electrocatalyst materials and belongs to a type of zeoliticim idazolate framework (ZIFs). Its bridging bond angle is 145°, which is consistent with the preferred bond angle of silicon-oxygen bonds in traditional zeolites. 2+ 、Co 2+ ) replaces the position of silicon, and the hydroxide anion replaces the position of oxygen to play a bridging role to form an open-ring tetrahedral unit, and repeatedly expands outward to form a porous network structure (Kaneti YV, Dutta S, Hossain MSA, et al. Strategies for improving the functionality of zeolitic imidazolate frameworks: tailoring nanoarchitectures for functional applications [J]. Advanced Materials, 2017, 29 (38): 1700213.). At present, there are many methods for synthesizing zeolitic imidazolate framework materials Zn2Co3 (OH) 10· Methods for preparing H2O materials, such as solvothermal method, sonochemical synthesis method, etc. (Feng S, Bu M, Pang J, et al. Hydrothermal stable ZIF-67 nanosheets via morphology regulation strategy to construct mixed-matrix membrane for gas separation [J]. Journal of Membrane Science, 2020, 593: 117404.; Beyer S, Prinz C, Schürrnann R, et al. Ultra-sonication of ZIF-67 crystals results in ZIF-67 nano-flakes [J]. Chemistry Select, 2016, 1 (18): 5905.5908.). This material can significantly catalyze the electrolysis of water and thus increase the yield of clean energy hydrogen, providing a new way for the research and development of electrocatalysts, and has potential research and application value.

[0004] A method for preparing Zn2Co3(OH) by microwave irradiation 10 The method of preparing Zn2Co3(OH)2O nanoparticles is to use analytical pure ZnSO4·7H2O and 2-methylimidazole as reaction raw materials, deionized water as solvent, and cetyltrimethylammonium bromide (CTAB) as surfactant, and use microwave radiation technology to prepare Zn2Co3(OH)2O nanoparticles. 10 ·H2O material. The microwave radiation method can adjust the reaction time, reaction temperature, reactant molar ratio and other experimental conditions to control the microscopic morphology of the target product, thereby obtaining high-quality Zn2Co3(OH) 10 ·H2O material. Target product Zn2Co3(OH) 10 The X-ray diffraction pattern (XRD pattern) of H2O material shows that the corresponding JCPDS card number is 21-1477, and the strongest peak corresponds to the hkl crystal plane index (002); the scanning electron microscope (SEM) pattern shows that the obtained Zn2Co3(OH) 10 The particle size of H2O material is small and the particles are uniform. XRD and SEM images fully prove that the Zn2Co3(OH) prepared by microwave radiation method involved in the present invention is 10 The H2O material has regular morphology and high purity, and is distinctively scientific, practical and novel. It is widely used in the fields of water electrolysis catalysts.

[0005] [Invention content]: The main contents of the present invention are as follows: (1) First, analytically pure Co(NO3)2·6H2O, ZnSO4·7H2O and 2-methylimidazole are used as reaction raw materials, deionized water is used as solvent, and hexadecyltrimethylammonium bromide (CTAB) is used as surfactant, and microwave radiation method is used to prepare Zn2Co3(OH) 10 ·H2O materials; (2) Microwave radiation method is easy to operate and has concentrated energy, which is beneficial to improve the reaction rate and Zn2Co3(OH) 10 ·H2O material yield; (3) by changing the molar ratio of the reaction raw materials, the amount of surfactant CTAB, the reaction time and the reaction temperature, the target product Zn2Co3(OH) 10 Precise control of the microstructure of H2O materials is beneficial for obtaining Zn2Co3(OH) that meets production needs 10 ·H2O material; (4) The target product Zn2Co3(OH) prepared by this patent 10 H2O materials can significantly catalyze the water electrolysis process, thereby increasing the yield of clean energy hydrogen, providing a new approach for the research and development of electrocatalysts and having potential research and application value.

[0006] [Technical solution of the present invention]: A method for preparing Zn2Co3(OH) by microwave radiation 10 The method of preparing Zn2Co3(OH)2O nanoparticles is to use analytically pure Co(NO3)2·6H2O, ZnSO4·7H2O and 2-methylimidazole as reaction raw materials, deionized water as solvent, and cetyltrimethylammonium bromide (CTAB) as surfactant to prepare Zn2Co3(OH)2O nanoparticles. 10 The H2O material is synthesized by microwave radiation method. The specific synthesis steps are as follows:

[0007] First, at room temperature, weigh 0.0100-5.0000 g of analytical pure Co(NO3)2·6H2O, 0.0100-5.0000 g of ZnSO4·7H2O and 0.0010-0.1000 g of hexadecyltrimethylammonium bromide (CTAB) and place them in a 100 mL beaker, add 5-60 mL of deionized water to the beaker, stir the solution clockwise with a glass rod for 5-10 min, place the solution on a magnetic stirrer, and stir at a speed of 300-600 rpm for 10-60 min to obtain a mixed solution A;

[0008] Second, weigh 1.0000-5.0000 g of 2-methylimidazole and place it in a 100 mL beaker, add 30-60 mL of deionized water thereto; stir with a glass rod for 3-5 minutes, place the solution on a magnetic stirrer, and stir at a speed of 300-600 rpm for 5-30 minutes to obtain solution B;

[0009] Third, the mixed solution A obtained in the first step is transferred to a 250 mL quartz round-bottom flask; the solution B obtained in the second step is uniformly added dropwise to the quartz round-bottom flask containing the mixed solution A at a rate of 0.0050 to 10.0000 mL / min. After the addition is completed, the solution is placed on a magnetic stirrer and uniformly stirred at a speed of 300 to 600 rpm for 5 to 60 min to obtain a mixed solution C;

[0010] Fourth, the mixed solution C obtained in the third step is transferred to a microwave reactor with a normal pressure reflux cooling device, the microwave reactor model is a Midea PJ21C-AU microwave reactor, the power after modification is 200-1400W, the frequency is 2450MHz; the heating temperature is set to 80-100°C, and the reaction time is 0.1-5.0h;

[0011] Fifth, after the reaction is completed, wait for the product in the quartz round-bottom flask to cool naturally to room temperature, transfer the product to a centrifuge, centrifuge at a speed of 4000-10000 rpm for 1-5 minutes, take out the lower layer product, wash it with deionized water for 3-5 times, and then wash it with ethanol for 3-5 times, then put the washed product in an oven, adjust the heating rate to 5°C / min, and keep it in an oven at 50-80°C for 5-24 hours to obtain the target Zn2Co3(OH) 10 ·H2O material; the X-ray diffraction results of the product show that the corresponding JCPDS card number is 21-1477, the strongest peak corresponds to the hkl crystal plane index (002), and the product unit cell parameters are α=γ=90.0° and β=100.7°; the morphology measured by scanning electron microscope (SEM) is nanoparticles with a diameter of 0.25 to 0.65 μm; the X-ray diffraction test results and scanning electron microscope (SEM) test results of the product fully prove that the material has a regular morphology and a small particle size, and is a functional material with excellent water electrolysis catalysis.

[0012] [Advantages and effects of the invention]: The patent of the invention relates to a method for preparing Zn2Co3(OH) by microwave radiation technology 10 ·H2O nanomaterial method, its advantages are: (1) Zn2Co3(OH) 10 H2O is a typical metal organic framework compound. Due to its ultra-high porosity and surface area, it is widely used in batteries, supercapacitors, catalysis, gas storage and separation. (2) The microwave radiation method used in this patent is simple to operate and has concentrated energy, which is conducive to improving the reaction rate and Zn2Co3(OH) 10·H2O material yield; (3) The microwave radiation method involved in the present invention can produce Zn2Co3(OH) with regular morphology and small particle size. 10 H2O materials have the potential for large-scale production and commercialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Zn2Co3(OH) 10 X-ray diffraction (XRD) pattern of H2O sample

[0014] Figure 2 Zn2Co3(OH) 10 ·13k times scanning electron microscope (SEM) image of H2O sample

[0015] Figure 3 Zn2Co3(OH) 10 ·50k times scanning electron microscope (SEM) image of H2O sample

[0016] Figure 4 Zn2Co3(OH) 10 ·50k times scanning electron microscope (SEM) image of H2O sample

[0017] Figure 5 Zn2Co3(OH) 10 ·50k times scanning electron microscope (SEM) image of H2O sample DETAILED DESCRIPTION

[0018] The following is a further description of the implementation and effects of the present invention in conjunction with the embodiments:

[0019] Example 1 Preparation of Zn2Co3(OH) using microwave radiation technology 10 H2O sample 1

[0020] At room temperature, 0.1747 g of analytical pure Co(NO3)2·6H2O, 1.7262 g of ZnSO4·7H2O and 0.0030 g of hexadecyltrimethylammonium bromide (CTAB) were weighed and placed in a 100 mL beaker. 6 mL of deionized water was added to the beaker. After being stirred clockwise for 10 min with a glass rod, the solution was placed on a magnetic stirrer and stirred at 500 rpm for 30 min to obtain a mixed solution A. Subsequently, 2.7107 g of 2-Methylimidazole was placed in a 100 mL beaker, and 42 mL of deionized water was added thereto; after stirring with a glass rod for 5 minutes, the solution was placed on a magnetic stirrer and stirred at a speed of 500 rpm for 30 minutes to obtain solution B; the mixed solution A was then transferred to a 250 mL quartz round-bottom flask; the obtained solution B was uniformly added dropwise to the quartz round-bottom flask containing the mixed solution A at a rate of 3.0000 mL / min. After the addition was completed, the solution was placed on a magnetic stirrer and stirred at a speed of 500 rpm for 20 minutes to obtain a mixed solution C; finally, the mixed solution C was transferred to a reflux cooling device with a normal pressure. The microwave reactor is a PJ21C-AU microwave reactor of Midea, and the power after modification is 1000W and the frequency is 2450MHz; the heating temperature is set to 100°C and the reaction time is 1.0h; after the reaction is completed, the product in the quartz round-bottom flask is naturally cooled to room temperature, and the product is transferred to a centrifuge, centrifuged at 8000rpm for 2min, the lower layer product is taken out, washed with deionized water 3 times, and then washed with ethanol 3 times, and then the washed product is placed in an oven, the heating rate is adjusted to 5°C / min, and the target Zn2Co3(OH) is obtained after being kept in an oven at 60°C for 24h. 10 ·H2O material; the X-ray diffraction results of the product show that the corresponding JCPDS card number is 21-1477, the strongest peak corresponds to the hkl crystal plane index (002), and the product unit cell parameters are α=γ=90.0° and β=100.7° ( Figure 1 ); Scanning electron microscopy (SEM) showed that the morphology was nanoparticles with a diameter of 0.25 to 0.65 μm ( Figure 2 to Figure 5 ); The X-ray diffraction test results and scanning electron microscope (SEM) test results of the product fully prove that the material has a regular morphology and a small particle size, and is a functional material with excellent water electrolysis catalytic performance.

[0021] Example 2 Preparation of Zn2Co3(OH) using microwave radiation technology 10 H2O sample 2

[0022] At room temperature, 0.1747 g of analytical pure Co(NO3)2·6H2O, 0.8631 g of ZnSO4·7H2O and 0.0030 g of hexadecyltrimethylammonium bromide (CTAB) were weighed and placed in a 100 mL beaker. 6 mL of deionized water was added to the beaker. After being stirred clockwise with a glass rod for 10 min, the solution was placed on a magnetic stirrer and stirred at 500 rpm for 30 min to obtain a mixed solution A. Subsequently, 2.7107 g of 2-Methylimidazole was placed in a 100 mL beaker, and 42 mL of deionized water was added thereto; after stirring with a glass rod for 5 minutes, the solution was placed on a magnetic stirrer and stirred at a speed of 500 rpm for 30 minutes to obtain solution B; the mixed solution A was then transferred to a 250 mL quartz round-bottom flask; the obtained solution B was uniformly added dropwise to the quartz round-bottom flask containing the mixed solution A at a rate of 3.0000 mL / min. After the addition was completed, the solution was placed on a magnetic stirrer and stirred at a speed of 500 rpm for 20 minutes to obtain a mixed solution C; finally, the mixed solution C was transferred to a reflux cooling device with a normal pressure. The microwave reactor is a PJ21C-AU microwave reactor of Midea, and the power after modification is 1000W and the frequency is 2450MHz; the heating temperature is set to 100°C and the reaction time is 1.0h; after the reaction is completed, the product in the quartz round-bottom flask is naturally cooled to room temperature, and the product is transferred to a centrifuge, centrifuged at 8000rpm for 2min, the lower layer product is taken out, washed with deionized water 3 times, and then washed with ethanol 3 times, and then the washed product is placed in an oven, the heating rate is adjusted to 5°C / min, and the target Zn2Co3(OH) is obtained after being kept warm in an oven at 60°C for 24h. 10 ·H2O material.

[0023] Example 3 Preparation of Zn2Co3(OH) using microwave radiation technology 10 H2O sample 3

[0024] At room temperature, 0.1747 g of analytical pure Co(NO3)2·6H2O, 1.2946 g of ZnSO4·7H2O and 0.0030 g of hexadecyltrimethylammonium bromide (CTAB) were weighed and placed in a 100 mL beaker. 6 mL of deionized water was added to the beaker. After being stirred clockwise for 10 min with a glass rod, the solution was placed on a magnetic stirrer and stirred at 500 rpm for 30 min to obtain a mixed solution A. Subsequently, 2.7107 g of 2-Methylimidazole was placed in a 100mL beaker, and 42mL of deionized water was added thereto; after stirring with a glass rod for 5 minutes, the solution was placed on a magnetic stirrer and stirred at a speed of 500rpm for 30 minutes to obtain solution B; then the mixed solution A was transferred to a 250mL quartz round-bottom flask; the obtained solution B was uniformly added dropwise to the quartz round-bottom flask containing the mixed solution A at a rate of 3.0000mL / min. After the addition was completed, the solution was placed on a magnetic stirrer and stirred at a speed of 500rpm for 20 minutes to obtain a mixed solution C; finally, the mixed solution C was transferred to a reflux cooling device with a normal pressure. The microwave reactor is a PJ21C-AU microwave reactor of Midea, and the power after modification is 1000W and the frequency is 2450MHz; the heating temperature is set to 100°C and the reaction time is 1.0h; after the reaction is completed, the product obtained in the quartz round-bottom flask is naturally cooled to room temperature, and the obtained product is transferred to a centrifuge, centrifuged at a speed of 8000rpm for 2min, the lower layer product is taken out, washed with deionized water 3 times, and then washed with ethanol 3 times, and then the washed product is placed in an oven, the heating rate is adjusted to 5°C / min, and the target Zn2Co3(OH) is obtained after being kept in an oven at 60°C for 24h. 10 ·H2O material.

Claims

1. Preparation of Zn2Co3(OH) by microwave irradiation 10 The method of preparing Zn2Co3(OH)2O nanoparticles is to use analytically pure Co(NO3)2·6H2O, ZnSO4·7H2O and 2-methylimidazole as reaction raw materials, deionized water as solvent, and hexadecyltrimethylammonium bromide as surfactant. 10 The H2O material is synthesized by microwave radiation method. The specific synthesis steps are as follows: First, at room temperature, weigh 0.0100-5.0000 g of analytical pure Co(NO3)2·6H2O, 0.0100-5.0000 g of ZnSO4·7H2O and 0.0010-0.1000 g of hexadecyltrimethylammonium bromide and place them in a 100 mL beaker, add 5-60 mL of deionized water to the beaker, stir the solution clockwise with a glass rod for 5-10 min, place the solution on a magnetic stirrer, and stir at a speed of 300-600 rpm for 10-60 min to obtain a mixed solution A; Second, weigh 1.0000-5.0000 g of 2-methylimidazole and place it in a 100 mL beaker, add 30-60 mL of deionized water thereto; stir with a glass rod for 3-5 minutes, place the solution on a magnetic stirrer, and stir at a speed of 300-600 rpm for 5-30 minutes to obtain solution B; Third, transfer the mixed solution A obtained in the first step into a 250 mL quartz round-bottom flask; The solution B obtained in the second step is uniformly added dropwise to the quartz round-bottom flask containing the mixed solution A at a rate of 0.0050-10.0000 mL / min. After the addition is completed, the solution is placed on a magnetic stirrer and uniformly stirred at a speed of 300-600 rpm for 5-60 min to obtain a mixed solution C; Fourth, the mixed solution C obtained in the third step is transferred to a microwave reactor with a normal pressure reflux cooling device, the microwave reactor model is a Midea PJ21C-AU microwave reactor, the power after modification is 200-1400W, the frequency is 2450MHz; the heating temperature is set to 80-100°C, and the reaction time is 0.1-5.0h; Fifth, after the reaction is completed, wait for the product in the quartz round-bottom flask to cool naturally to room temperature, transfer the product to a centrifuge, centrifuge at 4000-10000 rpm for 1-5 min, take out the lower layer product, wash it with deionized water 3-5 times, and then wash it with ethanol 3-5 times, then put the washed product in an oven, adjust the heating rate to 5°C / min, and keep it in an oven at 50-80°C for 5-24 hours to obtain the target Zn2Co3(OH) 10 H2O nanoparticle materials; The X-ray diffraction results of the product show that the corresponding JCPDS card number is 21-1477, the strongest peak corresponds to the hkl crystal plane index (002), and the product unit cell parameters are α=γ=90.0° and β=100.7°; the morphology thereof is measured by scanning electron microscope (SEM) and is nanoparticles with a diameter of 0.25 to 0.65 μm.

Citation Information

Patent Citations

  • Lithium ion battery negative material and preparation method and application thereof

    CN110600692A